2015
DOI: 10.1371/journal.pone.0137017
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Surface Modification Based on Functionalized Poly-P-Xylylene Coating

Abstract: The biotechnology to immobilize biomolecules on material surfaces has been developed vigorously due to its high potentials in medical applications. In this study, a simple and effective method was designed to immobilize biomolecules via amine-N-hydroxysuccinimide (NHS) ester conjugation reaction using functionalized poly-p-xylylene coating on material surfaces. The NHS ester functionalized coating is synthesized via chemical vapor deposition, a facile and solvent-less method, creating a surface which is ready … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The 50 ng/mL of BMP-2 immobilized nanofibers displayed the highest amount of calcium deposits among all nanofibers and cover glass, which indicates a higher degree of osteogenesis. 5 Compared to PCL and PCL/P3ANA nanofibers, the osteogenic activity of the cells was improved when they were cultured on 50 ng/mL of BMP-2 immobilized nanofibers, which demonstrates that the immobilized BMP-2 retains its activity. Culture of the cells on non-functionalized nanofibers is an evidence indicating the activity of the immobilized protein.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The 50 ng/mL of BMP-2 immobilized nanofibers displayed the highest amount of calcium deposits among all nanofibers and cover glass, which indicates a higher degree of osteogenesis. 5 Compared to PCL and PCL/P3ANA nanofibers, the osteogenic activity of the cells was improved when they were cultured on 50 ng/mL of BMP-2 immobilized nanofibers, which demonstrates that the immobilized BMP-2 retains its activity. Culture of the cells on non-functionalized nanofibers is an evidence indicating the activity of the immobilized protein.…”
Section: Resultsmentioning
confidence: 93%
“…ALP activity and Ca deposition are both osteogenic processes. 5 ALP is an enzyme which plays an important role in bone matrix mineralization process and therefore a good marker of osteogenic phenotype. 49 ALP activity of Saos-2 cells cultured for 3, 9, and 14 days on cover glass, PCL, PCL/P3ANA, and BMP-2/PCL/ P3ANA nanofibers is represented in Figure 10.…”
Section: Cytotoxicity Of Nanofibers and Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface of the material is the place where the material interacts with the host tissue . The interaction can be introduced either by the surface structure of the material or the substance released from the material. The process of surface modification not only alters the degradation and corrosion characteristics of materials but also the bioactivity of the materials. , We examined cell adhesion and spreading on the surface-treated materials. Twenty-four hours after the cells were seeded on the material, we found that cell adhesion and spreading were similar for all groups (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Regarding osteogenesis, fabricated scaffolds were cultured in osteogenic induction medium consisting of MEM-alpha (Thermo Fisher Scientific, USA) supplemented with 10% FBS (Biological Industries, Israel), 1% antibiotic-antimycotic (Biological Industries, Israel), 0.1 × 10 –6 M dexamethasone (Sigma-Aldrich, USA), 100 μg/mL l -ascorbic acid (Sigma-Aldrich, USA), and 10 × 10–3 M β-glycerol phosphate (Sigma-Aldrich, USA) . The osteogenesis activities of loaded hASCs were examined based on their ALP expression at day 7 analyzed by an alkaline phosphatase yellow (pNPP) liquid substrate system (Sigma-Aldrich, USA) and on calcium deposit formation for quantitative evaluation of calcium-based mineralization by freshly differentiated osteoblasts at day 21 by Alizarin red staining followed by dissolving in DMSO as in a previous study . The assay products were then analyzed using an ELISA spectrophotometer at wavelengths of 405 and 562 nm.…”
Section: Methodsmentioning
confidence: 99%